THE ROLE OF PROFITABILITY IN MODERATING THE EFFECT OF LEVERAGE, COMPANY SIZE AND INVESTMENT DECISIONS ON FIRM VALUE - Priyantoko, Mochammad Annas Dwi; Maryanti , Eny; Rahmadini, Elvara Rizky; Aprilia, Ayu Dwi (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the role of profitability in moderating the influence of leverage, company size, and investment decisions on firm value in food and beverage companies listed on the Indonesia Stock Exchange for the 2018-2020 period. Method: A quantitative with a purposive sampling approach, resulting in 51 company samples from 90 populations. Results: Leverage has no effect on firm value, company size has a significant negative effect on firm value, while investment decisions also have a significant negative effect. Profitability proves unable to moderate the relationship between leverage and investment decisions on firm value, but can moderate the significant negative effect of firm size on firm value. Novelty: The novelty of this study lies in testing the moderation of profitability in the relationship between firm size and firm value in the food and beverage sector. This study highlights that the size of leverage does not affect firm value because companies can rely on other capital, such as retained earnings, while large company size actually tends to reduce operational efficiency and attract less investor interest. High investment decisions are considered risky by investors, resulting in a decrease in firm value. Profitability only effectively moderates the relationship between firm size and firm value, strengthening the negative relationship between the two.